Occurrence and geochemistry of metamafic rocks from the Forquilha Eclogite Zone, central Ceara (NE Brazil): geodynamic implications - Amaral, Wagner da Silva; Saraiva Santos, Ticiano Jose; Wernick, Eberhard [UNESP] (Wiley-Blackwell, 2011)
In the northern region of the Borborema Province, a 30 km-long mafic/ultramafic belt of high pressure (HP) rocks called the Forquilha Eclogite Zone has been recently discovered in the Central Domain of Ceara State. The belt comprises three groups of rocks: ( I) garnet amphibolites, (2) retrograded eclogites and (3) clinopyroxene-garnet amphibolites, all of them being hosted in garnet +/- kyanite + sillimanite schists and orthogneisses which are often migmatized. The geochemical analyses of 30 representative samples confirm differences among the three groups that were initially classified by petrography. The garnet amphibolites are the most depleted rocks, with relatively flat rare earth element (REE)(PM) pattern and (SPIDER)(PM) pattern with negative Rb, Th, Nb, Sr and Zr anomalies. It is the most fractionated group, ranging from picrobasalts to andesites. Fractional crystallization and mineral accumulation are indicated by Eu and Sr anomalies. The data show geochemical affinities with,. island-arc basalts. The retrograded eclogites display flat (REE)(PM), but without Eu anomalies. Nb/La ratios are low and variable, as for slightly enriched MORB from ocean floor or intra-oceanic back-arc environments. However, a genetic link with the Group 1 rocks cannot be completely discarded. The clinopyroxene-garnet amphibolites are the most enriched group. (REE)(PM) and (SPIDER)(PM) patterns show many features of alkaline basalts. In the Nb/Yb versus Th/Yb diagram the data cluster near the E-MORB standard. Several geochemical aspects of these rocks fit well those from the HP/UHP Pan-African/Brasiliano Suture Zone in the Dahomeyides/Hoggar regions of West Africa. However, differences in their extent and lack of alignment preclude a direct correlation among these zones. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: Borborema Province; Brazil; HP/UHP; retrograded eclogites; Pan-African belt; geochemistry